PENINGKATAN KEMAMPUAN BERHITUNG ANAK MELALUI PERMAINAN CONGKLAK MODIFIKASI DI TAMAN KANAK-KANAK HUSNUL KHOTIMAH KOTA BENGKULU - Suryati; Rismareni Pransiska (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to determine the improvement of early numeracy skills in Group A children at TK Husnul Khotimah Bengkulu City through modified congklak games. This research used Classroom Action Research (CAR) with the Kemmis & McTaggart model. The subjects were 15 students of Group A. The study was conducted in 2 cycles over 2 months, from March to April 2026. Data were collected through observation and documentation, then analyzed using percentage techniques. The results showed that in Cycle I, children's numeracy skills were still low: 12.5% for counting 1-10, 18.75% for the concept of more-less, and 16.25% for simple addition. After reflection and action improvement in Cycle II by simplifying the congklak holes, adding number cards 1-5, and using two-colored seeds, children's numeracy skills increased significantly. In Cycle II, 85.50% of children were able to count 1-10, 88.5% understood the concept of more-less, and 91.25% could perform simple addition with the criteria of Very Well Developed (VWD).